Evaluation of stitched fabric composite processed by RTM in quasi-static test - Shiino, Marcos Yutaka [UNESP]; Hilario Cioffi, Maria Odila [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP] (Elsevier B.V., 2011)
Stitched fabrics have been widely studied for potential application in aircraft structures since stitch yarns offer improvements in the out-of-plane mechanical properties and also can save time in the lay up process. The down side of stitch yarns came up in the manufacturing process of fabric in which defects introduced by the needle movement creating fiber-free-zones, fiber breakage and misalignment of fibers. The dry stitched carbon fabric preform has mainly been used in the Resin Transfer Molding (RTM) process which high fiber content is aimed, those defects influence negatively the injection behavior reducing the mechanical properties of final material. The purpose of this research work focused on testing in quasi-static mechanical mode (in-plane tension) of a monocomponent resin CYCOM (R) 890 RTM/carbon fiber anti-symmetric quadriaxial fabric stitched by PE 80Dtex yarn processed by RTM. The evaluation consisted in comparing the scatter of the quasi-static test with the attenuation of ultrasonic maps, which show the path of the resin and possible dry spots considering that interference of yarn in resin flow is detectable in ultrasonic measurement. Microscopic analysis was also considered for further evaluation in case of premature failure. (C) 2011 Published by Elsevier Ltd. Selection and peer-review under responsibility of ICM11
Keywords: Carbon/epoxy composites; resin transfer molding (RTM); flexural test; ultrasonic test